Pemanfaatan CRISPR dalam Pengembangan Vaksin Generasi Baru terhadap Virus Tropis - Bagus Kusuma Ardi; Abdul Muchlis (Journal of New Trends in Sciences, 2025)
The development of vaccines for tropical viruses such as dengue and Zika presents a significant challenge in global health. These viruses not only cause serious health complications but also impact health systems and economies in tropical countries. CRISPR/Cas9 technology offers an innovative solution to accelerate vaccine development by enabling precise gene editing. This study aims to explore the potential of CRISPR in accelerating the design and production of vaccines for tropical viruses. The method used in this study is a laboratory-based experimental design involving genetic engineering, with dengue and Zika virus genome models. The first step involves identifying virus target genes using the CRISPR/Cas9 system, which allows the detection of specific genes involved in pathogenesis and immune responses. Subsequently, genetic constructs are designed to generate vaccine candidates that can efficiently and precisely target pathogens. The resulting vaccines are tested in vitro in cell cultures to observe immune responses and their effectiveness against virus infections. The results show that CRISPR not only accelerates the process of identifying and engineering vaccine genes but also significantly improves vaccine production efficiency. CRISPR-based vaccines demonstrate higher immunogenicity compared to conventional methods, thus holding potential as the foundation for developing faster and safer next-generation vaccines. However, this study also identifies challenges related to off-target effects and the efficient delivery of CRISPR components, which require further research to ensure safety and efficacy in human clinical applications.